Digital Health Record Systems or Applications in the Management of Type 2 Diabetes: A Literature Review - Amaya Patron, Irma Alejandra; Nieto Hipólito, Juan Iván; Vasquez Briseño, Mabel; Navarro Cota, Christian Xavier; Avilés Rodríguez, Gener José (International Journal of Online and Biomedical Engineering (iJOE), 2025)
This literature review examines the integration of digital health record systems in the management of diabetes mellitus (DM), particularly type 2 diabetes, and highlights the urgent need for improved patient access to health information through technology. The use of information technology (IT) in the management of diabetes has shown remarkable results, such as increased medication adherence (12.8%–39%), lower HbA1c (0.49%–8%) levels, and lower blood pressure (47.2%–30.8%) levels. It also explores the benefits of mobile health (mHealth) applications, electronic health records (EHR), and personal health records (PHR) in improving self-management and healthcare support via social networks. It emphasizes the need for regular monitoring and communication facilitated by robust IT solutions that enable patients to access and share their health data, ensure effective communication, and support health monitoring. Unlike other reviews, we focus exclusively on proposals that facilitate interaction with medical records for automatic access to patient data. Our main contribution focuses on identifying critical needs to improve diabetes management through technology.